Understanding the extent of contraceptive non-use among women at risk of unintended pregnancy, National Survey of Family Growth 2011-2017 - Brittni N. Frederiksen; Katherine Ahrens (Elsevier, 2020)
Objective: To describe characteristics of U.S. contraceptive non-users to inform tailored contraceptive access initiatives. Study design: We used National Survey of Family Growth data from 2011 to 2017 to identify characteristics of contraceptive non-users compared to other women ages 15-44 at risk for unintended pregnancy. We also examined reasons for not using contraception by when non-users expected their next birth. We calculated unadjusted and adjusted prevalence ratios using two definitions of contraceptive non-use: (1) contraceptive non-use during the interview month, and (2) a more refined definition based on contraception use during the most recent month of sexual intercourse and expectation of timing of next birth. We considered p-values <0.05 statistically significant. Results: Approximately 20% (n=2844) of 12,071 women at risk of unintended pregnancy were classified as standard contraceptive non-users. After adjusting for all other variables, non-users were more likely to be low-income, uninsured, never married, expect a birth within 2 years, and have zero or one parity. The top reasons for contraceptive non-use were not minding if they got pregnant (22.6%), worried about contraceptive side effects (21.0%), and not thinking they could get pregnant (17.6%). After applying the more refined non-user definition, we identified 5.7% (n=721) of women as non-users; expecting a birth within 2-5 years and having a parity of one were associated with non-use after adjustment of all other factors. Conclusion: Our more refined definition of non-users could be used in future studies examining the causes of unintended pregnancy and to inform programmatic interventions to reduce unintended pregnancy. Implications: Describing contraceptive non-users and reasons for contraceptive non-use could help us better understand reasons for unintended pregnancy and inform tailored contraceptive access initiatives.